2020
DOI: 10.1101/2020.06.12.149484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brief Report: Test-Retest Reliability of Explicit Auditory Processing Measures

Abstract: In this brief report, we examined the test-retest reliability of our in-house explicit auditory processing measures in the context of 30 L1 and L2 English users. The participants took the same test battery which consisted of a total of four discrimination tasks (encoding acoustic details of formant, pitch, duration, and rise time) and two reproduction tasks (repeating novel melodic and rhythmic patterns) at Days 1 and 2. According to the results, the participants' initial and second test scores demonstrated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…This indicates that, although the task format of the auditory processing tests has been well accepted (see also Moore, 2012, for an overview of auditory processing test formats in L1 and hearing research), the possibility of delivering the test online remains open to further discussion, validation, and refinement. We stress again that the results of the reliability analyses derived from our small‐scale pilot research (Saito et al., 2020b, for 30 L1 and L2 English speakers). In order to better establish the presence or absence of satisfactory test–retest reliability, we plan to redo the analyses with a larger sample size with greater statistical power.…”
Section: Limitations and Future Directionsmentioning
confidence: 52%
See 1 more Smart Citation
“…This indicates that, although the task format of the auditory processing tests has been well accepted (see also Moore, 2012, for an overview of auditory processing test formats in L1 and hearing research), the possibility of delivering the test online remains open to further discussion, validation, and refinement. We stress again that the results of the reliability analyses derived from our small‐scale pilot research (Saito et al., 2020b, for 30 L1 and L2 English speakers). In order to better establish the presence or absence of satisfactory test–retest reliability, we plan to redo the analyses with a larger sample size with greater statistical power.…”
Section: Limitations and Future Directionsmentioning
confidence: 52%
“…It is important to note that the results suggested that some parts of our online testing of auditory abilities ( r = .907–.775 for spectral and temporal reproduction) reached an acceptable level of test–retest reliability (as identified by Lance, Butts, & Michels, 2006) as well as reaching the level of test–retest reliability previously reported for in‐laboratory testing (for example, r = .75 in Raz, Willerman, & Yama, 1987). However, the low reliability of the other measures ( r = .598 and .284 for spectral and temporal discrimination) could be ascribed to several scenarios (e.g., the lack of validity, small sample size, and inconsistent sound system across participants; for more details and open data, see Saito, Sun, & Tierney, 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we acknowledge that the construct validity of the auditory processing measures (i.e., A×B discrimination) remains unclear. As pointed out in the existing literature (Snowling, Gooch, McArthur, & Hulme, 2018), the task format inevitably taps into not only participants' auditory perception skills, but also may rely upon a range of modality-general cognitive abilities (e.g., working memory, attention control; for further discussion, see Saito et al, 2020). In order 39 PERCEPTUAL FOUNDATIONS OF LATE BILINGUALISM to further examine the unique contribution of auditory perception to L2 learning, future studies should adopt not only auditory processing but also cognitive ability tasks.…”
Section: Discussionmentioning
confidence: 99%
“…For all the audio materials used in the tests, and the results of test-retest reliability, see our brief research report (Saito, Sun, & Tierney, 2020).…”
Section: Motivation For Current Studymentioning
confidence: 99%
“…As for the composite auditory processing scores (averaging pitch, duration, and rise time discrimination), the reliability (r = .720) could be considered satisfactory and comparable to similar research (e.g., r = 0.75 in Raz, Willerman, & AUDITORY PROCESSING & VOCABULARY Yama, 1987). The results suggest that although using individual test scores may result in low reliability (e.g., duration discrimination), composite test scores may serve as a more reliable proxy of one's auditory precision (for methodological details, see Brief Report in Saito, Sun, & Tierney, 2020b).…”
Section: Auditory Processing Measuresmentioning
confidence: 99%